(Effect of sowing dates on growth, forage and grain yield of three oats cultivars (Avena sativa L - Al-Juheishy, Waleed K. S.; Gazal, Salim A. Y. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted in winter season of 2012 -2013 at two locations, Fields of College of Agriculture and Forestry-Mosul University and in Al-Hamidat/village of Thaljah (20 km) west of Mosul city. The study aimed to investigate the effect of sowing dates (1 , 15 , 30 November) on the growth, forage and grain yield of three varieties from Oat (ICARDA Tall, Kangaroo, and ICARDA Short) using randomized complete block design (split plot system) with three replications. The results showed the first sowing date (1/11) in most growth characteristics, dry forage yield and grain yield components, The highest dry yield at Mosul location 6.15 ton .ha-1 and at 5.57 ton.ha-1 at Thaljah location, And the highest grain yield in the Mosul location 1.86 ton.ha-1 and at Thaljah location 1.62 ton .ha-1. ICARDA Tall was superior in dry forage at both locations and gave 6.52 ton .ha-1 at Mosul location and 6.05 ton.ha-1 at Thaljah location. While Kangaroo topped the grain yield with 2.05 ton.ha-1 location Mosul and 2.14 ton.ha-1 at location Thaljah. The highest grain yield interaction between variety kangaroo with sowing dates of the (1/11) at bath at location in Mosul location2.16 ton.ha-1 and 2.25 ton.ha-1 at location Thaljah While the interaction between the variety ICARDA Tall and the sowing dates (1/11) gave the highest dry forage yield at Mosul location 7.56 ton.ha-1 and 6.43ton.ha-1 at Thaljah location.